An Unconditional Quantile Regression Based Decomposition of Spatial Welfare Inequalities in Ghana. - Agyire-Tettey, Frank; Ackah, Charles Godfred; Asuman, Derek (Journal of Development Studies, 2018)
Ghana has witnessed tremendous economic growth since the 1990s and attained the Millennium Development Goals target of halving poverty. This notwithstanding, inequality in Ghana increased over the same period, suggesting growth benefits were not equitably distributed. This study provides evidence on the determinants of household consumption expenditure and factors that explain rural-urban welfare gaps between 1998 and 2013. The study employs an unconditional quantile regression and recently proposed decomposition technique based on re-centred influence functions. We find significant spatial differences in consumption expenditure across selected quantiles, with rural-urban inequalities driven largely by differences in returns to households' endowments.